Thoughts on borders: what lessons can be learned from African literacy processes in the light of Paulo Freire's conceptions? - Sousa, Cirlene Cristina de (2021)
The text is supported by a bibliographic research on the frontiers of Paulo Freire's thought and his encounters with Africa from several of his works. Initially, the political and ideological conditions that led Paulo Freire to be imprisoned by the 1964 dictatorship in Brazil are addressed, due to his revolutionary educational proposals. His trip to exile in Chile, where he published his most famous work “Pedagogia do Oprimido”, ended up leading Freire to get involved in the struggles of other Latin American and African peoples. In the specific case of the African continent, his experiences have reshaped his pedagogy and his practice as an educator. The article is divided into two parts, namely: in the first, the meaning of Freirean literacy is worked on in its encounter with Africa. In the second, a short history of the challenges and achievements of this meeting is outlined. Finally, it is noted that Paulo Freire's education, due to its political and emancipatory character, influenced the educational policies of African countries that became independent. In conclusion, it is emphasized that it is legitimate to say that Paulo Freire's “speeches” are mixed with the experiences he lived in Africa, as it is not difficult to perceive African influences in his way of being, being, doing and living together. To understand Paulo Freire as a frontier intellectual means to say that his thinking has been changing due to time and the historical context that is inserted. The actuality of his thinking is not restricted to social, cultural and political boundaries. Hence the greatness of his legacy.